PREPARATION AND CHARACTERIZATION OF FLY ASH ADDITIVE MODIFIED POLIESTER BASED MEMBRANE - Efendi, Januar; Aprilia, Sri; Djuned, Fauzi M (Jurnal Rekayasa Kimia & Lingkungan, 2023)
Recently, Polyethersulfone (PES) polymer material based on flat sheet membranes reached much attention in membrane technology. However, PES polymer has low hydrophilicity. This study describes PES-based membranes incorporating fly ash as an additive. The first analysis was conducted by Fourier Transform Infrared, Scanning Electron Microscope, tensile strength, and porosity tests. Four membranes, including pure PES membranes, were prepared via the phase inversion process, namely MA0, MA0.1, MA1, and MS1. The characteristics of the membrane samples were analyzed in terms of chemical group, morphology, mechanical and membrane surface hydrophilicity. The characterization results show that additive incorporation increased pure water flux performance, and the highest pure water permeability increased up to 70% by the MA1 membrane. Moreover, it increased by 19% compared to pure silica-modified PES membrane (MS1). In addition, the MA-1 membrane at a pressure of 3 bar reached significant performance in the trend of pure water flux values because of these improvements in membrane characteristics. The membrane also shows a higher tensile strength with adding additives to the membrane prepared.